2021
DOI: 10.1039/d0sc06162j
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic enantioselective synthesis of macrodiolides and their application in chiral recognition

Abstract: An asymmetric tandem Friedel–Crafts alkylation/intermolecular macrolactonization of ortho-quinone methides with C3-substituted indoles was achieved by using a chiral N,N′-dioxide-scandium(iii) complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…These results demonstrated that ferric ions (Fe 3+ ) could be selectively recognized by δ-carboline derivative 4a. 12 …”
Section: Resultsmentioning
confidence: 99%
“…These results demonstrated that ferric ions (Fe 3+ ) could be selectively recognized by δ-carboline derivative 4a. 12 …”
Section: Resultsmentioning
confidence: 99%
“…The electrophilic aromatic C–H bond functionalization provides one of the most direct approaches to aryl derivatives, and plays an irreplaceable role in organic synthesis. 1 Generally, the electrophilic reagents are essential to the efficiency and selectivity of these reactions, affording one new C–C (Friedel–Crafts reaction) 2 or C–X (halogenation, 3 nitrogenation, 4 sulfonation 5 ) bond within one step in these electrophilic reactions. From the aspect of synthesis-efficiency and step-economy, 6 the development of electrophilic reactions to deliver complex molecules 7 along with multi-chemical bond construction under practical and mild reaction conditions is still highly desirable, and has been the pursuing goal of chemists.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different classes of macrocycles, macrolactones are especially unique compounds that exhibit biological activities and often function as enzyme inhibitors; they also showed applications in molecular recognition for supramolecular chemistry. For example, macrolactones synthesized from cholesterol derivatives have shown utility for molecular recognitions [ 8 ], and a synthetic macrodilactone exhibited enantioselective recognition of amino alcohols, as well as metal ions [ 9 ]. Naturally existing carbohydrate-based macrolactones or macrolides often exhibit many desirable biological activities for drug development [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%